Reconstruction of seismic data based on SFISTA and curvelet transform - Tian, Lin; Qin, Si (Frontiers in Earth Science, 2023)
In seismic data processing, the reconstruction and interpolation of missing traces are an essential task. To overcome the limitations of irregularly sampled seismic data, this paper proposes a seismic data interpolation method combining the smoothing fast iterative soft threshold algorithm (SFISTA) and Curvelet transform, this method uses Curvelet domain as sparse domain, for comparing, Contourlet transform is used for different sparse domain, and the fast iterative shrinkage-thresholding algorithm (FISTA) is used for different optimization algorithm. The numerical modeling and real data show that the SFISTA method in Curvelet domain can give better reconstruction effects and higher reconstruction accuracy than that of in Contourlet domain with the FISTA method, in addition, the SFISTA method in Curvelet domain can be used to reconstruct the missing traces of three-dimensional seismic data.